Struktur Sekretori Tanaman Bahan Ramuan Obat Diabetes - . Dorly (Institut Pertanian Bogor, 2006)
Anatomical structure of medicinal plants wich are used in diabetic therapy is not yet completely identified. This research was conducted to study the structure of their secretory tissues. Observation of anatomical structure of leaves was done by making paradermal and transversal sections, while observation of anatomical structure of stem, fruits, and rhizomes were performed by making transversal sections. Microscopic observation found several types os secretory structure in plant organs observed. Glandular hairs were found in kiurat (Plantago mayor L.) leaves, sambiloto (Andrographis paniculata (Burm.f) Wallich ex Nees) leaves, and kumis kucing (Orthosiphon aristatus (Blume) Miq.) leaves; lithocysts cell were found in sambiloto leaves; oil cavity/cells were found in salam (Syzygium polyanthim (Wight) Walp.) leaves, jambu (Psidium guajava L.) leaves, lada (Piper nigrum L.) fruits, and jahe (Zingiber officinale Roscoe) rhizomes; idioblast cells wich contained starch grains were found in brotowali (Tinospora crispa (L.) Miers) stems, lada fruits, and jahe rhizomes; and latex cells were found in brotowali stems.